2022
DOI: 10.3390/foods11121804
|View full text |Cite
|
Sign up to set email alerts
|

Bioactive Compounds and Antioxidant Activity of Red and White Wines Produced from Autochthonous Croatian Varieties: Effect of Moderate Consumption on Human Health

Abstract: Moderate wine consumption is often associated with healthy lifestyle habits. The role of wine as a healthy drink is mainly due to its bioactive compounds, which differ according to various viticultural and enological factors. The aim of the present study was to observe the differences in bioactive compounds of white and red autochthonous Croatian wines, differing in terms of the grape variety and production technology. Our further aim was to explore the effect of their moderate consumption (200 mL per day) ove… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
16
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(18 citation statements)
references
References 62 publications
1
16
0
1
Order By: Relevance
“…Nevertheless, the concentrations of precursors and thus of varietal thiols in Pošip wine could possibly be increased if the grapes were harvested at their full maturity. The grapes used in this study yielded a relatively low alcohol content (Table 1) for wines from this grape variety, considering previous studies reporting values higher than 13 vol% (Tomašević et al, 2017;Jagatić Korenika et al, 2019;Tomašević et al, 2019;Radeka et al, 2022).…”
Section: Resultsmentioning
confidence: 90%
“…Nevertheless, the concentrations of precursors and thus of varietal thiols in Pošip wine could possibly be increased if the grapes were harvested at their full maturity. The grapes used in this study yielded a relatively low alcohol content (Table 1) for wines from this grape variety, considering previous studies reporting values higher than 13 vol% (Tomašević et al, 2017;Jagatić Korenika et al, 2019;Tomašević et al, 2019;Radeka et al, 2022).…”
Section: Resultsmentioning
confidence: 90%
“…Phenolic acids include benzoic acid, cinnamic acid and their derivatives [3,4]. Moderate wine consumption contributes to a healthy lifestyle [5], improves lipoprotein metabolism, lowers cardiovascular mortality risk [6,7], protects the brain and nerve cells and reduces platelet aggregation [8]. Red wine polyphenolic extract consumption can be used in the prevention and treatment of chronic diseases, such as metabolic syndrome, degenerative pathologies and cancer [9].…”
Section: Introductionmentioning
confidence: 99%
“…However, the results of several studies associate regular consumption of wine in moderate amounts with beneficial cardiovascular effects and a low incidence of deaths from atherosclerosis and coronary heart disease, effects related to increased levels of high-density lipoprotein (HDL), but which have not always been confirmed in the case of white wine [ 2 , 6 , 12 , 13 , 14 , 15 ]. Despite numerous studies referring to the beneficial effects of red wine, Radeka et al, have shown that white wines, not just red wines, have produced a decrease in systolic and diastolic blood pressure, total cholesterol and LDL levels, and an increase in HDL levels and serotonin and dopamine levels, following regular consumption for six weeks [ 16 ]. Moreover, moderate wine consumption (200–300 mL/day), both for red and white wine, is generally associated with a reduction in all-cause mortality, with studies highlighting some of the beneficial effects, such as regulating blood pressure, cholesterol and lipids, anti-inflammatory and anti-tumor effects, preventing diabetes, obesity, atherosclerosis, cardiovascular and neurodegenerative diseases [ 2 , 6 , 14 , 15 , 16 ].…”
Section: Introductionmentioning
confidence: 99%
“…Despite numerous studies referring to the beneficial effects of red wine, Radeka et al, have shown that white wines, not just red wines, have produced a decrease in systolic and diastolic blood pressure, total cholesterol and LDL levels, and an increase in HDL levels and serotonin and dopamine levels, following regular consumption for six weeks [ 16 ]. Moreover, moderate wine consumption (200–300 mL/day), both for red and white wine, is generally associated with a reduction in all-cause mortality, with studies highlighting some of the beneficial effects, such as regulating blood pressure, cholesterol and lipids, anti-inflammatory and anti-tumor effects, preventing diabetes, obesity, atherosclerosis, cardiovascular and neurodegenerative diseases [ 2 , 6 , 14 , 15 , 16 ]. Although chronic exposure to ethanol induces up-regulation of hepatic antioxidant enzymes in mice, the beneficial effects of red wine are thought to exceed those attributed especially to alcohol [ 17 , 18 ].…”
Section: Introductionmentioning
confidence: 99%